2008
DOI: 10.1590/s0004-27492008000600014
|View full text |Cite
|
Sign up to set email alerts
|

Visual control in children with developmental dyslexia

Abstract: Purpose: To assess binocular control in children with dyslexia. Methods: Cross-sectional study with 26 children who were submitted to a set of ophthalmologic and visual tests. Results: In the dyslexic children less eye movement control in voluntary convergence and unstable binocular fixation was observed. Conclusion: The results support the hypothesis that developmental dyslexia might present deficits which involve the magnocellular pathway and a part of the posterior cortical attentional network. ABSTRACT INT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
2
7
0
1
Order By: Relevance
“…This finding is in keeping with published work, 14,15 but a number of studies, including a study of 86 children with dyslexia and controls and a descriptive review, have found contrasting results, 16,[20][21][22] all of whom described no association between dyslexia and stereoacuity.…”
Section: Depth Perceptionsupporting
confidence: 88%
See 3 more Smart Citations
“…This finding is in keeping with published work, 14,15 but a number of studies, including a study of 86 children with dyslexia and controls and a descriptive review, have found contrasting results, 16,[20][21][22] all of whom described no association between dyslexia and stereoacuity.…”
Section: Depth Perceptionsupporting
confidence: 88%
“…19,20 However, other studies have found no association between these abnormalities and dyslexia. 2,16,18,[20][21][22][23] A descriptive review of 114 articles published from 2000 to 2012 found that eye movement anomalies, visual contrast deficits, and pseudoneglect were the main ophthalmic features associated with dyslexia. 24 It has been hypothesized that the abnormalities in eye movements are potentially the result, not the cause, of the condition.…”
Section: What This Study Addsmentioning
confidence: 99%
See 2 more Smart Citations
“…For fusional vergence, the findings are again not consistent. Castro found that children with dyslexia had poor positive (base-out) fusional vergence (Castro, Salgado, Andrade, Ciasca, & Carvalho, 2008) whereas others have found normal positive but reduced negative (base-in) fusional vergence (Bucci et al, 2008;Kapoula et al, 2007;Palomo-Alvarez & Puell, 2010). It has also been reported that children with dyslexia have reductions in both positive and negative fusional vergence (Bucci, Melithe, Ajrezo, Bui-Quoc, & Gerard, 2014;Evans et al, 1994b;Heim, Haugen, Helland, & Fostervold, 2004).…”
Section: Introductionmentioning
confidence: 99%